Within‐person fluctuations in stressful life events, sleep, and anxiety and depression symptoms during adolescence: a multiwave prospective study. (17th March 2020) - Vidal Bustamante, Constanza M.; Rodman, Alexandra M.; Dennison, Meg J.; Flournoy, John C.; Mair, Patrick; McLaughlin, Katie A.
Abstract : Background: Adolescence is characterized by substantial changes in sleep behavior, heightened exposure to stressful life events (SLEs), and elevated risk for internalizing problems like anxiety and depression. Although SLEs are consistently associated with the onset of internalizing psychopathology, the mechanisms underlying this relationship remain poorly understood, especially at the within‐person level. Here, we leverage a high‐frequency longitudinal design to examine sleep as a potential mechanism linking SLEs to increases in anxiety and depression symptoms over a one‐year period. Methods: Thirty female adolescents aged 15–17 years completed 12 monthly in‐laboratory assessments of exposure to SLEs and symptoms of anxiety and depression ( n  = 355 monthly assessments), and wore an actigraphy wristband for continuous monitoring of sleep for the duration of the study ( n  = 6, 824 sleep days). Multilevel models examined concurrent and lagged within‐person associations between SLEs, sleep duration and timing regularity, and anxiety and depression symptoms. Results: Within‐person fluctuations in SLEs were associated with variability in sleep duration both concurrently and prospectively, such that when adolescents experienced greater SLEs than was typical for them, they exhibited more variable sleep duration that same month as well as the following month. In turn, within‐person increases in sleep duration variability predicted greater anxiety symptoms in the same month and mediated the association between SLEs and anxiety. Conclusions: These findings highlight sleep disruptions as a mechanism underlying the longitudinal associations between SLEs and anxiety symptoms, and suggest that interventions promoting sleep schedule consistency may help mitigate risk for stress‐related psychopathology in adolescence.